Learning and the infant mind - Woodward, Amanda; Needham, Amy.; Oxford eBooks (Oxford : Oxford University Press, 2009)
Until recently there has been little contact between investigations of how infants learn and what infants know. The authors consider both infants' knowledge across domains, and learning, bringing to bear direct laboratory manipulations of learning and more general considerations of the relations between experience and knowledge.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Learning, Psychology of; Infant psychology; Cognition in infants; Electronic books